Empowering Indigenous Communities to Understand and Preserve the Syntactic Structure of the Using Ethnic Language - Afriani, Imro’atul Husna; Rahman, Abd.; Yudiana, I Kadek; Pradana, Dian Arief; Rohmah, St. Shabibatul; Anwar, Saiful (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
This Community Service activity aims to empower the Using indigenous community in Banyuwangi Regency to understand and preserve the Using language, particularly its syntactic structure, which includes phrases, clauses, and sentences. The main problems faced by the community are that the use of the Using language remains largely intuitive, without explicit understanding of syntactic rules, and that community-based linguistic assistance is still very limited. The approach employed in this activity is an educational and participatory approach through linguistic mentoring. The activities were conducted in the form of counseling sessions, group discussions, practical analysis of everyday utterances, and the use of visual media in the form of simple syntactic trees. The mentoring materials focused on introducing the structure of nominal, verbal, adjectival, adverbial, and prepositional phrases, as well as contextual understanding of clauses and sentences in the Using language. The results of the activity indicate an increase in community understanding and awareness of the syntactic structure of the Using language. In addition to enhancing linguistic knowledge, this activity also strengthens the community’s sense of ownership of the Using language as part of their local cultural identity and supports sustainable efforts to preserve regional languages.